THERAPEUTIC POTENTIAL AND APPLICATIONS OF BIOGLASS: A REVIEW - SRAVANI, VADNALA; VIDYAVATHI, M. (International Journal of Applied Pharmaceutics, 2025)
Bioglass has emerged as a revolutionary biomaterial because of its bioactivity, biocompatibility, and capacity to form a bond with both hard and soft tissues. Originally, Dr. Larry Hench in the late 1960s developed. Bioglass, which has proven especially effective in bone regeneration, dental restoration, and wound healing, positioning it as a versatile material for various medical applications. Unlike traditional bioinert materials, bioglass fosters a beneficial biological response when in contact with physiological environments, forming a hydroxyl carbonate apatite [HCA] layer on its surface that mimics natural bone mineral. This bioactivity, combined with its customizable composition, has enabled the development of various bioglass types tailored for specific applications. In this review, fundamental properties that contribute to bioglass effectiveness and primary healthcare applications of bioglass, focusing on its role in bone grafts, dental fillers, and coatings for implants discussed. Furthermore, this review explore its promising applications in wound healing, where bioglass dressings offer accelerated tissue repair and reduced infection risks. The main objective of this review is to provide a thorough insight into bioglass, with a focus on its present-day uses in the medical field.